Partial denitrification providing nitrite: Opportunities of extending application for anammox. (October 2019) - Du, Rui; Peng, Yongzhen; Ji, Jiantao; Shi, Liangliang; Gao, Ruitao; Li, Xiangchen
Abstract: Anaerobic ammonium oxidation (anammox) has been extensively investigated for cost-efficient nitrogen removal from wastewater. However, the major issues of nitrate (NO3 − -N) residue and instability in the current combination of nitritation and anammox process necessitates being addressed efficiently. The recently proposed partial-denitrification (PD), terminating NO3 − -N reduction to nitrite (NO2 − -N), has been regarded as a promising alternative of NO2 − -N supplying for anammox bacteria. Given the engineering practices, the steadily high NO2 − -N production, alleviating organic inhibition, and reducing greenhouse gas of PD process offers a viable and efficient approach for anammox implementation. Moreover, it allows for the extending applications of anammox process due to the NO3 − -N removal availability. Here we comprehensively review the important new outcomes and discuss the emerging applications of PD-based anammox including the process development, mechanism understanding, and future trends. Significant greater stability and enhanced nitrogen removal efficiency have been demonstrated in the novel integrations of PD and anammox process, indicating a broad perspective in dealing with the mainstream municipal sewage, ammonia-rich streams, and industrial NO3 − -N contained wastewater. Furthermore, researches are still needed for the predictable and controllable strategies, along with the detailed microbiological information in future study. Overall, the achievement of PD process provides unique opportunity catalyzing the engineering applications of energy-efficient and environmental-friendly wastewater treatment via anammox technology. Highlights: Partial-Denitrification provides a stable and efficient alternative for nitrite supply. PD process offers extending application of anammox treating nitrate wastewater. PD/A holds potential in improved efficiency for mainstreams and sidestreams treatment. Emerging opportunities are given for wastewater treatment engineering by PD/A. Predictable controlling strategies and penetrating microbial mechanism are needed.